Sera from Adult Patients with Cystic Fibrosis Contain Antibodies to Pseudomonas aeruginosa Type III Apparatus - Moss, Joel (American Society for Microbiology, 2001)
Expression of type III proteins of Pseudomonas aeruginosa in patients with cystic fibrosis (CF) was investigated by measuring the immune response against components of the type III pathway. Twenty-three of the 33 sera contained antibodies against PcrV, a protein involved in translocation of type III cytotoxins into eukaryotic cells, and 11 of 33 had antibodies against ExoS, while most CF sera contained antibodies against PopB and PopD, components of the type III apparatus. These data indicate that P. aeruginosa commonly expresses components of the type III translocation apparatus in adult CF patients.